2022
DOI: 10.5802/crchim.140
|View full text |Cite
|
Sign up to set email alerts
|

10,000 urinary stones for 10 years of analysis: a retrospective study in western Switzerland

Abstract: Several studies have reported a worldwide increase in incidence and prevalence of nephrolithiasis, with some specificities across countries and regions. A retrospective review was performed on all urinary calculi submitted between 2009 and 2019 from a large part of the western Switzerland to our laboratory. A total of 10,437 stones were analysed and the presence of 18,804 compounds revealed. The median age of patients was 51 years and the global male-to-female ratio was 2.49:1. From 2009 to 2019, calcium oxala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
2
0
0
Order By: Relevance
“…The male predisposition to CaOx may be attributed to the following factors: the influence of testosterone and dihydrotestosterone on CaOx crystal formation in rat models 22 , the promotion of CaOx crystal formation by enhanced androgen receptor (AR) signaling in hepatocytes 23 , 24 , as well as factors such as heavy physical work, excessive sweating, inadequate fluid intake, and concentrated urine volume 25 . Furthermore, the incidence of UA was higher in men compared to women, with a male-to-female ratio of 5.75:1, which is consistent with previous studies 26 , 27 . Additionally, our study aligns with previous research, indicating a higher incidence of ST and CaP in women 17 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The male predisposition to CaOx may be attributed to the following factors: the influence of testosterone and dihydrotestosterone on CaOx crystal formation in rat models 22 , the promotion of CaOx crystal formation by enhanced androgen receptor (AR) signaling in hepatocytes 23 , 24 , as well as factors such as heavy physical work, excessive sweating, inadequate fluid intake, and concentrated urine volume 25 . Furthermore, the incidence of UA was higher in men compared to women, with a male-to-female ratio of 5.75:1, which is consistent with previous studies 26 , 27 . Additionally, our study aligns with previous research, indicating a higher incidence of ST and CaP in women 17 .…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the risk of UTI tends to increase in women during menopause after the age of 50, when estrogen levels significantly decline, which may contribute to the development of infectious stones in older women 29 . Our study observed similar trends to previous research conducted in China 5 , 18 and other countries 26 , 30 , we further employed the Kruskal–Wallis test and multiple comparison tests. This approach allowed us to offer a more detailed and comprehensive statistical analysis of the variations in stone occurrence among different age groups (Fig.…”
Section: Discussionsupporting
confidence: 82%